1983
DOI: 10.1172/jci110984
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte phenotype and function in pseudolymphoma associated with Sjögren's syndrome.

Abstract: A B S T R A C T Lymph node (LNL) and salivary gland lymphocytes (SGL) from three patiernts with pseudolymphoma and primary Sj6gren's syndrome (loSS) were characterized with monoclonal antibodies to demonstrate (a) a predominance of T cells (>80%) reactive with anti-T cell antibodies OKT4 (>70%) and OKT8 (<20%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…The specific role of IgA anticardiolipin antibodies in the pathogenesis of Sjogren's syndrome remains unclear. One possible function of the IgA autoantibodies is to help clear cellular debris derived from normal cell turnover, cells destroyed by the immune system, or from potential pathogens within the gland.28 It is likely that IgA anticardiolipin antibodies are made at the salivary gland inflammatory site, as other autoantibodies are produced by lymphocytes eluted from the salivary gland.29 30 As the salivary gland in patients with Sjogren's syndrome is a mucosal site of inflammation, it is likely that local T helper cells facilitate the isotype switch from IgM to IgA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of IgA anticardiolipin antibodies in the pathogenesis of Sjogren's syndrome remains unclear. One possible function of the IgA autoantibodies is to help clear cellular debris derived from normal cell turnover, cells destroyed by the immune system, or from potential pathogens within the gland.28 It is likely that IgA anticardiolipin antibodies are made at the salivary gland inflammatory site, as other autoantibodies are produced by lymphocytes eluted from the salivary gland.29 30 As the salivary gland in patients with Sjogren's syndrome is a mucosal site of inflammation, it is likely that local T helper cells facilitate the isotype switch from IgM to IgA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be attributed to several factors, including the relatively small number of patients reported with lymphoma and ascertainment bias in patient referral patterns. However, these differences also may reflect the difficulty in distinguishing lymphoma from extensive infiltrates due to "benign" SS or pseudolymphoma [9]. The lymphomas are predominantly non-Hodgkin's B cell (IgM-K) tumors that arise in the salivary gland and cervical lymph nodes.…”
Section: Development Of Lymphoma In Ssmentioning
confidence: 99%
“…This disorder is particularly well-suited to serve as a model for autoimmune endocrine-exocrine disease, since it is relatively common and the target organs (i.e., salivary glands) are safely accessible to biopsy (9,lO). Studies using monoclonal antibodies and in vitro functional studies have shown that the saliv,ary gland is infiltrated predominantly by T cells of the Leu-3a-positive (OKT4+) subset that have T helperhnducer cell function (10)(11)(12). The salivary glands of these patients are active sites of autoantibody and interleukin-2 (IL-2) production (13,14).…”
Section: Hla-dr By Salivary Gland Epithelial Cells Robert I Fox Thomentioning
confidence: 99%